Differences in ball speed and three-dimensional kinematics between male and female handball players during a standing throw with run-up - Serrien, B.; Clijsen, R.; Blondeel, J.; Goossens, M.; Baeyens, J.-P. (BMC Sports Science, Medicine and Rehabilitation, 2015)
Background